2015
DOI: 10.1246/cl.150408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thieno[3,2-b]benzofurans by Palladium-catalyzed Intramolecular C–H/C–H Coupling

Abstract: The intramolecular CH/CH coupling of 3-aryloxythiophenes and 3-aryloxybenzo [b]thiophenes has been found to occur effectively in the presence of Pd(TFA) 2 and AgOAc as catalyst and oxidant, respectively, to afford the corresponding cyclized products, thieno [3,2-b] 2 The syntheses of TBF 3 and BTBF 4 were carried out only by some conventional multistep methods. For instance, the mother TBF and BTBF were obtained from the combinations of 3-chloro-2-formylbenzo[b]furan/2-mercaptoacetate ester and methyl thiosali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…The structures of these novel planar π-conjugated compounds 2a-d were fully characterized on the basis of 1 H-NMR, 13 C-NMR spectra (see Figure S1-8 in the Supporting Information). [36][37] Simultaneously, the structures of 2a-d were further established on the basis of the base peak molecular ion at m/z [M + ] 369.00 for 2a, 508.11 for 2b, 456.04 for 2c and 482.13 for 2d in their mass spectra. All results were consistent with the proposed structures.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of these novel planar π-conjugated compounds 2a-d were fully characterized on the basis of 1 H-NMR, 13 C-NMR spectra (see Figure S1-8 in the Supporting Information). [36][37] Simultaneously, the structures of 2a-d were further established on the basis of the base peak molecular ion at m/z [M + ] 369.00 for 2a, 508.11 for 2b, 456.04 for 2c and 482.13 for 2d in their mass spectra. All results were consistent with the proposed structures.…”
Section: Introductionmentioning
confidence: 99%
“…7 Meanwhile, we recently reported that thieno[3,2-b]-benzofuran frameworks can be readily constructed by the palladium-catalyzed dehydrogenative cyclization of 3-phenoxythiophenes. 8 A series of thienobenzofurans 1c−e prepared by our method could be employed as the substrates in the present alkenylation. Thus, the corresponding 2-styrylthienobenzofurans 3ca−ea were obtained under the standard room-temperature conditions (Table 2, entries 7−9).…”
mentioning
confidence: 99%
“…This method is straightforward and highly step-economical, enabling us to produce condensed (hetero)acenes from rather simple polyarenes, in which several aromatic units are connected with each other through appropriate linker units [2][3][4][5][6][7][8][9][10][11]. Recently, we reported the synthesis and optical properties of a series of furan-fused aromatics via the formal dehydrogenative coupling adopting oxygen atom as the linker [12][13][14][15][16][17]. In particular, bisbenzofuro [2,3- were found to exhibit intense photoluminescence with relatively high quantum efficiency (Φ flu up to 0.70), indicating that the BBFZPy scaffold may serve as a key fluorophore unit in certain light-emitting functional materials (Scheme 1) [14].…”
Section: Introductionmentioning
confidence: 99%